2013
DOI: 10.1002/smj.2116
|View full text |Cite
|
Sign up to set email alerts
|

Unmixed signals: How reputation and status affect alliance formation

Abstract: We analyze how incumbents in technology-driven industries are influenced by founders' reputation and status when considering strategic alliances with newly emerging firms. We theorize that reputation and status represent two distinct components of perceived quality that exert independent and interdependent effects on alliance formation. Using literature on impression formation processes to derive predictions of signal congruence, we argue that the independent effects of reputation and status are amplified when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 93 publications
(110 reference statements)
7
138
1
Order By: Relevance
“…If an actor has not already established his or her position in the status hierarchy, they more likely to be discounted in the future, even when their performance equals that of their high 31 status counterparts. Thus, status bias "unjustifiably victimize[s]" low status actors (Merton 1968: 59), preventing them from being treated as if they were operating in an even playing field.Our findings extend our understanding of the halo effect by showing that status is especially likely to lead to over-recognition of quality when status and reputation are aligned (Stern et al 2013). The importance of aligning expectations in the evaluator's mind may be one reason that other scholars have found that status has its greatest effect on economic performance advantages when there is consistency among multiple status signals (Zhao and Zhou 2011).…”
supporting
confidence: 72%
“…If an actor has not already established his or her position in the status hierarchy, they more likely to be discounted in the future, even when their performance equals that of their high 31 status counterparts. Thus, status bias "unjustifiably victimize[s]" low status actors (Merton 1968: 59), preventing them from being treated as if they were operating in an even playing field.Our findings extend our understanding of the halo effect by showing that status is especially likely to lead to over-recognition of quality when status and reputation are aligned (Stern et al 2013). The importance of aligning expectations in the evaluator's mind may be one reason that other scholars have found that status has its greatest effect on economic performance advantages when there is consistency among multiple status signals (Zhao and Zhou 2011).…”
supporting
confidence: 72%
“…Second, we expand recent attempts to examine the interplay between reputation and other types of signals (Ertug & Castellucci, 2013;Jensen & Roy, 2008;Stern, Dukerich, & Zajac, 2014) by showing that such interplay is dependent on contextual constraints imposed by the level of accountability audiences face. As we elaborate in our discussion section, these findings have broad and important theoretical and practical implications for research on reputation.…”
Section: Introductionmentioning
confidence: 72%
“…These accounts imply that the effects of reputation might be independent of, and not contingent on, that of status. However, more recent research suggests that reputation and status can enhance one another because together they provide additional information that reduces uncertainty (Stern et al, 2014). Our stance is that the presence and degree of such interplay between reputation and status is audience-specific.…”
Section: Theoretical Contributionsmentioning
confidence: 87%
See 2 more Smart Citations